USAHA UNTUK MENINGKATKAN LOYALITAS TOKO KELONTONG DALAM MENGHADAPI USAHA RITEL YANG MENJAMUR DI MASYARAKAT - Yuningrum, Heny (Economica: Jurnal Ekonomi Islam, 2016)
The economics competition was happened fastly now.Seperti halnya usaha ritel yang sekarang ini menjamur. As the ritel business like mushroomed now.Toko Kelontong have been drowning than the ritel business. The drowning of Toko kelontong in the public while give decline result of their income. This research while discuss about how to increasing the customer loyality of toko kelonotong or traditional shop to competitied with the ritel shop.The type of this article is qualitative research with the explanatory or libarary research and Â to summarize the more research. And the finally can get the solution for traditional shop..This result of this research are was see more thing was doing the ritel shop like the cleaness and the comfortable of place, the completely of product, give the promotion of product, give the friendly service, give the low price than ritel shop, give the more innovation on the store, setting of product more neatly, the government must give the solution the problem solving of their competition, and needs the relationship of ritel shop and traditional shop.